Eficácia da reabilitação fonoaudiológica na disfagia orofaríngea em pacientes pós-acidente vascular cerebral - Drozdz, Daniela Rejane Constantino (2013)
The rehab in neurogenic dysphagia based on evidences imply in the relation between interventions and the results. Aim: evaluate the efficacy of speech therapy intervention in swallowing of carrier patients of swallowing disorders after stroke, examine the grade of swallowing, the level of anxiety and the nutritional state of carrier patients of swallowing disorders after stroke, before and after speech therapy treatment. Methods: Exploratory study, transverse of quantitative character. The sample consisted in 12 patients, media of age 64.6 years with medical diagnosis of hemorrhagic and ischemic stroke without cognitive disorders. It was realized clinical assessment of dysphagia with the partial use of the Protocol of Risk Assessment for Dysphagia (PARD), application of the Functional Oral Intake Scale for Dysphagia in Stroke Patients FOIS, videofluoroscopy assessment of swallowing, questionnaire about perception swallowing, application of Beck Anxiety Scale(BAI) and application of mini nutritional assessment MNA®. All tests were applied before and after speech therapy (15 sessions) Results: Statistically significant changes in the degree of dysphagia through clinical assessment (p=0,017) and oral intake through FOIS (p=0,003).On videofluoroscopy assessment and perception of swallowing it wasn`t observed statistics results, but it was possible to observe an evolution in their scores, 33% showed functional swallowing and 25% characterized swallowing with excellency after the therapy sessions. It was observed during assessments pre speech therapy that 47.1% of the patients showed picture of malnutrition and 35.3% of patients had a mild degree of anxiety. After fifteen treatment sessions it was found that 16.7% were malnourished and 50% of patients had minimal degree of anxiety. Conclusion: It was observed therapy efficacy on dysphagias after stroke on this sample, evolution on the level of oral intake and in the grade of dysphagia, also confirmed by videofluoroscopy. In relation to the grade of anxiety and to the nutritional state of this sample, there was an considerable evolution after therapeutic procedure. Although the sample number is small, the reached progress in all variables showed importance of use of a therapeutic program, providing benefits in life quality of the dysphagic patient.